Ferroptosis-Related Gene Contributes to Immunity, Stemness and Predicts Prognosis in Glioblastoma Multiforme - Dong, Jiawei; Zhao, Hongtao; Wang, Fang; Jin, Jiaqi; Ji, Hang; Yan, Xiuwei; Wang, Nan; Zhang, Jiheng; Hu, Shaoshan (Frontiers in Neurology, 2022)
Ferroptosis, a recently discovered regulated programmed cell death, is associated with tumorigenesis and progression in Glioblastoma. Based on widely recognized ferroptosis-related genes, the regulation of ferroptosis patterns and corresponding characteristics of immune infiltration of 516 GBM samples with GSE13041, TCGA-GBM and CGGA-325 were comprehensively analyzed. Here, we revealed the expression, mutations and CNV of ferroptosis-related genes in GBM. We identified three distinct regulations patterns of ferroptosis and found the hub genes of immunity and stemness among DEGs in three patterns. A prognostic model was constructed based on five ferroptosis-related genes and verified at the mRNA and protein level. The risk score can not only predict the prognosis but also the degree of immune infiltration and ICB responsiveness by functional annotation. The overall assessment of ferroptosis-related genes in GBM patients will guide direction of improved research and develop new prognostic prediction tools.